Feasibility study on partial insulation winding technique for the development of self-protective MgB2 magnet. (June 2018) - Kim, Y.G.; Kim, J.C.; Kim, J.M.; Yoo, B.H.; Hwang, D.Y.; Lee, H.G.
Highlights: Feasibility of using the partial insulation winding technique for MgB2 MRI magnet. Development of a self-protective MgB2 MRI magnet. Charge-discharge and quench tests for a partial insulation MgB2 magnet. Self-protecting behavior of partial insulation MgB2 magnet. Required time to charge 0.5-T/300-mm PI MgB2 magnet. Abstract: This study investigates the feasibility of using the partial insulation winding technique for the development of a self-protective MgB2 MRI magnet with a fast charge-discharge rate. Charge-discharge and quench tests for a prototype PI MgB2 magnet confirmed that the magnet was successfully operated at full-field performance and exhibited self-protecting behavior in the event of a quench. Nonetheless, the required time to charge the 0.5-T/300-mm PI MgB2 magnet was almost five days, implying that the charge-discharge delay of the PI MgB2 magnet still needs to be ameliorated further to develop a real-scale MgB2 MRI magnet with a fast charge-discharge rate.